Pengabdian Masyarakat Melalui Inovasi Asma: Upaya Pengurangan Polusi Asap dari Pembakaran Sampah di Desa Plodongan - Lathifah, Hidayah Nur; Khaurani, Sabrina Zahron; Miqdad, Miqdad; Anjani, Diva Nurhaliza; Basuki, Karina; Azzahra, Fauzan Bahy; Amanda, Salmah Putri; Maulida, Hilda Ulfa; Alfatih, Birru Farras; Mahardika, Ahimsa; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Waste management remains a serious problem in Plodongan Village due to limited facilities and a lack of an adequate handling system. Residents generally burn waste openly because it is considered easy and inexpensive, but this method causes air pollution and health risks. This community service activity presents an innovative Smoke-Free Waste Incinerator (ASMA) as a solution to reduce air pollution while increasing combustion efficiency. The methods used include observation, planning, tool construction, outreach, mentoring, and evaluation. The ASMA is designed using a modified metal barrel with an optimal air circulation system to produce more complete combustion and significantly less smoke. The results of the questionnaire evaluation showed that more than 50% of residents considered the ASMA effective in reducing waste accumulation and air pollution. This innovation is expected to be the first step in creating more environmentally friendly and sustainable waste management.